Differential gene expression of the three natriuretic peptides and natriuretic peptide receptor subtypes in human liver. Issue 1 (January 1997) - Vollmar, A M; Paumgartner, G; Gerbes, A L
Abstract : BACKGROUND: Various effects of atrial natriuretic peptide (ANP) on the liver have been observed. However, there is limited information about the types of receptors for natriuretic peptides expressed by the human liver. AIM: To investigate gene expression of the three NP receptor types (NPR) as well as of the NP in human liver. METHODS: Presence of mRNA coding for all three NPR and for ANP, brain and C-type natriuretic peptide (BNP, CNP) was investigated by reverse transcription-polymerase chain reaction (RT-PCR). Human liver tissues and hepatocellular carcinoma tissues were examined. RESULTS: Specific PCR products for all three NPR, namely NPR-A, B, and C, could be detected. Moreover, ANP and CNP, but not BNP mRNA was detectable. The concentration of ANP transcripts was up to fivefold higher in hepatocellular carcinoma compared with non-tumorous liver tissue of the same subjects. No difference in the expression of NP receptors relative to GAPDH mRNA of tumorous and non-tumorous tissue was observed except of slightly increased NPR-A transcripts. CONCLUSION: These data show that NPR transcripts are coexpressed with ANP and CNP mRNA in the human liver. This provides evidence for a local NP system in the human liver.